Pemerkasaan peranan masjid di Malaysia era kontemporari / Nor Azlina Abd. Wahab, Norafifah Ab. Hamid and Norajila Che Man - Abd. Wahab, Nor Azlina; Ab. Hamid, Norafifah; Che Man, Norajila (2016)
The history of Prophet Muhammad’s struggle in spreading Islam has proved the importance of the mosque as a basis for the construction of sovereign Muslim State (Madinah al-Munawwarah). At that time, the mosque is not just a place of worship, but also the center for scholarly activities – main references for Islamic affairs and bring together scholars to convey the teaching of Islam, and as a social agent in society. Referring to the success of the mosque at the time of Prophet Muhammad (pbuh) the role and function of mosques in Malaysia should be strengthened optimally to cater the needs of contemporary Islamic society. Therefore, this conceptual paper aims to study the roles of mosque in developing the ummah as well as to suggest its role as one stop center in Malaysia. For this paper, methods of observation and content analysis have been used. Preliminary finding shows that preparation and arrangement of various activities and programs can intrigue the target group especially the young generations.